Development of a broad-based ADME panel for use in pharmacogenomic studies. (June 2014) - Brown, Andrew MK; Renaud, Yannick; Ross, Colin; Hansen, Mark; Mongrain, Ian; Valois, Diane; Carleton, Bruce C; Hayden, Michael R; Dubé, Marie-Pierre; Tardif, Jean-Claude; Phillips, Michael S
Aim: To optimally address the interindividual variability observed in pharmacokinetic drug response, we have created a custom genotyping panel that interrogates most of the key genetic variations present in a set of 181 prioritized genes responsible for the absorption, distribution, metabolism and excretion (ADME) of many therapeutic agents. This consensus list of genes and variants was based on the ADME core and extended gene lists compiled by a group of pharmaceutical companies as having relevance. Although these pharmacokinetic genes and pathways are well known, tools that can interrogate a large number of these genes simultaneously within a single experiment are not currently available.Methods: Using novel design strategies, we have developed an optimized and validated ADME genotyping panel, encompassing approximately 3000 variants, that has broad applicability to any study or clinical trial that would benefit from the evaluation of an extensive list of ADME genes.Results & conclusion: Over the course of three design iterations, overall assay conversion rates were improved from 83 to 97% resulting in a panel that fills in many of the gaps in coverage present on currently available commercial genotyping assays. The utility of the assay has been demonstrated by the screening of more than 1000 samples resulting in the discovery of novel pharmacogenomic associations. The assay, and the underlying methods, will continue to be a valuable tool for use in future pharmacogenomic studies. Original submitted 28 November 2013; Revision submitted 13 May 2014